If it's not what You are looking for type in the equation solver your own equation and let us solve it.
77+(-2x)=89+(-4x)
We move all terms to the left:
77+(-2x)-(89+(-4x))=0
We get rid of parentheses
-2x-(89+(-4x))+77=0
We calculate terms in parentheses: -(89+(-4x)), so:We get rid of parentheses
89+(-4x)
determiningTheFunctionDomain (-4x)+89
We get rid of parentheses
-4x+89
Back to the equation:
-(-4x+89)
-2x+4x-89+77=0
We add all the numbers together, and all the variables
2x-12=0
We move all terms containing x to the left, all other terms to the right
2x=12
x=12/2
x=6
| 3(0.5x-4)=3/4x-1.2 | | 2(3w+6)/5=-11 | | –14+10p=4+9p | | 66+4x-40=90 | | -3w-7w=10 | | -10/1x=5 | | a^2-8a=-2 | | 5x=27;x= | | -7(2t+1)=-7 | | 3x+5=8x(6-5x) | | x−0.5x=1.2 | | -6x-20=4-6(6x-6) | | 6/8x=-3 | | 34q=-16 | | 17+x/4=18 | | 100f=(100)(0.272727 | | 69-1x=94-6x | | 6+2r-4=9r+8-5r | | (8u+5)=0 | | 1=2x3=116 | | 112=2x;x= | | (8u+5)(4u-5)=0 | | -15-2n=5(8n-2)-5 | | 2.25x+15=9.5+0.5 | | -8(s+5)=-108 | | ^2x-3/4=9 | | 12(4+8n)=-2(7+8n) | | 8x=23;x= | | 9e=90 | | 36+4u=49 | | 8(6x-2)=14* | | -77-5=x |